From the Boardroom to the War Room : America's Corporate Liberals and FDR's Preparedness Program - Holl, Richard E. (Book collections on Project MUSE., 2017)
Between World War I and World War II, America's corporate liberals experienced a profound ideological change. In the 1920s, corporate liberals embraced company-specific solutions to economic problems. They believed that if every company, in every industry, employed advanced managerial techniques -- such as granting workers non-wage benefits to increase their job satisfaction -- employment, production, and profits could be stabilized and prosperity sustained indefinitely. The Great Depression, of course, made a mockery of this idyllic vision. Corporate liberals admitted that private efforts failed to maintain the nation's economic health, ultimately endorsing large-scale government intervention to bail out the stricken economy. By 1935, the corporate liberal conversion from privatism to business-government partnership was well under way. Corporate liberals served President Franklin Roosevelt throughout the Depression and preparedness periods. Marion Folsom of Eastman Kodak Corporation, Edward Stettinius, Jr. of United States Steel, and others joined New Deal agencies struggling to re-employ workers and bring about social security. Later, at Roosevelt's request, they entered emergency preparedness bodies to ready the United States for the possibility of war. When Japan attacked Pearl Harbor on December 7, 1941, the reconfigured American economy (which the corporate liberals had done so much to create) proved capable of mass producing weapons and other equipment. The bottom line, staunchly revisionist in nature, is that the corporate liberals ran an effective mobilization campaign, overcoming isolationist resistance to rearmament, Roosevelt's reluctance to grant them genuine authority, and other constraints. Richard E. Holl is Professor of History at the Lees College Campus of Hazard Community and Technical College. His latest article, on Axis prisoners of war in Kentucky, won the Collins Award of the Kentucky Historical Society.